2014
DOI: 10.1007/s00420-014-0946-5
|View full text |Cite
|
Sign up to set email alerts
|

Occupational kneeling and squatting: development and validation of an assessment method combining measurements and diaries

Abstract: ObjectivesAs knee-straining postures such as kneeling and squatting are known to be risk factors for knee disorders, there is a need for effective exposure assessment at the workplace. Therefore, the aim of this study was to develop a method to capture knee-straining postures for entire work shifts by combining measurement techniques with the information obtained from diaries, and thus avoiding measuring entire work shifts. This approach was applied to various occupational tasks to obtain an overview of typica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 28 publications
0
13
1
Order By: Relevance
“…Similarly, a 63% increased odds of knee OA was observed in builders and floor layers. It has been shown that floor layers kneel and squat for a large proportion of their working time, especially during gluing and filling, thereby generating high external knee forces . The prevalence of patellofemoral radiologic changes and prepatellar, infrapatellar bursitis, however, does not seem to increase in floor layers .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, a 63% increased odds of knee OA was observed in builders and floor layers. It has been shown that floor layers kneel and squat for a large proportion of their working time, especially during gluing and filling, thereby generating high external knee forces . The prevalence of patellofemoral radiologic changes and prepatellar, infrapatellar bursitis, however, does not seem to increase in floor layers .…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have examined the relationship between physically demanding occupations such as farming , mining , and floor laying and the onset of knee OA. The underlying mechanistic links between occupations and knee OA are believed to be biomechanical, with excessive knee forces generated during strenuous work tasks . Several studies have identified frequent workplace kneeling, squatting, and heavy lifting as risk factors for development and progression of knee OA .…”
Section: Introductionmentioning
confidence: 99%
“…3739 Kneeling is an important activity for a number of occupations, including floor laying, roofing, joinery, nursery teaching, painting and decorating, plumbing and cleaning. 40 Systematic reviews have found evidence that occupational kneeling is a risk factor for osteoarthritis, suggesting that kneeling ability may be a particularly important occupational factor for patients after TKR. 41,42…”
Section: Impactmentioning
confidence: 99%
“…The postural data and durations for the different tasks were determined by segmenting the 4-h data into the individual tasks observed. The individual task segments were then used in addition to the documented schedule for a characteristic 8-h work day and calculated as a shift value for the percentages of body angles for each assessment day using the method verified by Ditchen et al (2014).…”
Section: Data Processing and Evaluationmentioning
confidence: 99%